Plasma polymerized nanoparticles are a safe platform for direct delivery of growth factor therapy to the injured heart - Clayton, Zoë E.; Santos, Miguel; Shah, Haisam; Lu, Juntang; Chen, Siqi; Shi, Han; Kanagalingam, Shaan; Michael, Praveesuda L.; Wise, Steven G.; Chong, James J. H. (Frontiers in Bioengineering and Biotechnology, 2023)
Heart failure due to myocardial infarction is a progressive and debilitating condition, affecting millions worldwide. Novel treatment strategies are desperately needed to minimise cardiomyocyte damage after myocardial infarction and to promote repair and regeneration of the injured heart muscle. Plasma polymerized nanoparticles (PPN) are a new class of nanocarriers which allow for a facile, one-step functionalization with molecular cargo. Here, we conjugated platelet-derived growth factor AB (PDGF-AB) to PPN, engineering a stable nano-formulation, as demonstrated by optimal hydrodynamic parameters, including hydrodynamic size distribution, polydisperse index (PDI) and zeta potential, and further demonstrated safety and bioactivity in vitro and in vivo. We delivered PPN-PDGF-AB to human cardiac cells and directly to the injured rodent heart. We found no evidence of cytotoxicity after delivery of PPN or PPN-PDGFAB to cardiomyocytes in vitro, as determined through viability and mitochondrial membrane potential assays. We then measured contractile amplitude of human stem cell derived cardiomyocytes and found no detrimental effect of PPN on cardiomyocyte contractility. We also confirmed that PDGF-AB remains functional when bound to PPN, with PDGF receptor alpha positive human coronary artery vascular smooth muscle cells and cardiac fibroblasts demonstrating migratory and phenotypic responses to PPN-PDGF-AB in the same manner as to unbound PDGF-AB. In our rodent model of PPN-PDGF-AB treatment after myocardial infarction, we found a modest improvement in cardiac function in PPN-PDGF-AB treated hearts compared to those treated with PPN, although this was not accompanied by changes in infarct scar size, scar composition, or border zone vessel density. These results demonstrate safety and feasibility of the PPN platform for delivery of therapeutics directly to the myocardium. Future work will optimize PPN-PDGF-AB formulations for systemic delivery, including effective dosage and timing to enhance efficacy and bioavailability, and ultimately improve the therapeutic benefits of PDGF-AB in the treatment of heart failure caused by myocardial infarction.